Fantasy and Judgement: Brides’ Intimate Talk on Facebook - Feyza Akınerdem (European Journal of Turkish Studies)
This article explores how women’s judgement towards each other draws fantasies for a happy marriage through the medium of a Facebook group’s wall. Gelin Evleri ve Çeyizleri (Brides’ Home and Trousseau) is a closed Facebook group where Turkish-speaking women exchange their ideas, feelings, and judgements about married life. Women, anonymous or with their real identities, use this technological medium to interact with each other, to share images of their domestic lives and to engage in intimate conversation. I followed the posts which appeared on the group’s wall from September to December 2018 and narrowed my focus to two categories of posts: first, posts about romantic fantasies and settings, and second, posts which seek advice about one-on-one relationships between couples. Fantasies that are embedded in the conversations on the group’s wall are catalysts for judgements. In other words, women come to terms with the norm of the family through fantasies, while also problematizing the level of men’s emotional investment in relationships.